Developing Key Performance Indicators from Mission and Vision Statements of an Engineering College in Oman (Global Journal of Management and Business Research, 2014)
The purpose of this paper is to trace the method of developing the Key Performance Indicators (KPI) from the Mission and Vision statements of an Engineering College in Muscat, Oman. In this context, KPIs provides parameters for measuring the quality and standards of the institute. For an educational institute the KPIs extend into areas that are beyond the realm of financial fields as the primary aim here is to develop students from the high schools in to responsible and capable engineers and the monitory returns, perhaps, take a very important second position status
Keywords: KPI; stakeholders; engineering college